Influence of myosteatosis on survival of patients with pancreatic cancer: A systematic review and meta-analysis - Xin Zhang; Licheng Wei; Jiangguo Li; Yuexia Deng; Wei Xu; Dongkui Chen; Xing Li (iScience)
Summary: The present meta-analysis aims to evaluate the impact of myosteatosis on overall survival (OS) and progression-free survival (PFS) in patients with pancreatic cancer (PC). A comprehensive literature search was conducted in the Medline, Web of Science, and Embase databases. The hazard ratio (HR) and corresponding 95% confidence interval (CI) for the association between myosteatosis and survival outcomes were pooled using a random-effects model. A total of 14 studies were included. The pooled analysis demonstrated that myosteatosis was significantly associated to poorer OS (HR: 1.50, 95% CI: 1.35–1.67, p < 0.001; I2 = 0%). The subgroup analysis revealed consistent results across various study characteristics, including geographic regions, cancer stages, follow-up durations, and study quality. In addition, myosteatosis was associated to worse PFS (HR: 1.34, 95% CI: 1.15–1.57, p < 0.001; I2 = 34%). The present meta-analysis indicates that myosteatosis is associated to significantly worse OS and PFS in patients with PC.